2009
DOI: 10.1001/archgenpsychiatry.2009.156
|View full text |Cite
|
Sign up to set email alerts
|

Brain Monoamine Oxidase A Binding in Major Depressive Disorder

Abstract: Elevated MAO-A binding after SSRI treatment indicates persistence of a monoamine-lowering process not present in health. This provides a strong conceptual rationale for continuing SSRI treatment during early remission. Greater MAO-A binding in the prefrontal and anterior cingulate cortex in subjects with MDD in recovery and its association with subsequent recurrence argue that deficient monoamine neuromodulation may persist into recovery and contribute to recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(54 citation statements)
references
References 66 publications
(90 reference statements)
3
44
0
Order By: Relevance
“…Altogether, our results demonstrate that insufficient dietary iron supply can establish molecular features that resemble several neurological disorders, such as abnormal ferritin accumulation in striatum observed in parkinsonian syndromes and Huntington disease (Vidal et al, 2004; Simmons et al, 2007), increased MAO-A activity in prefrontal cortex which is associated with depression (Meyer et al, 2009) and increased degree of lipid peroxidation in hippocampus that is related with most of conformational diseases (Sultana et al, 2013). By showing these molecular alterations, this study emphasizes the importance of adequate iron supplementation for brain health and prevention of neurological diseases.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Altogether, our results demonstrate that insufficient dietary iron supply can establish molecular features that resemble several neurological disorders, such as abnormal ferritin accumulation in striatum observed in parkinsonian syndromes and Huntington disease (Vidal et al, 2004; Simmons et al, 2007), increased MAO-A activity in prefrontal cortex which is associated with depression (Meyer et al, 2009) and increased degree of lipid peroxidation in hippocampus that is related with most of conformational diseases (Sultana et al, 2013). By showing these molecular alterations, this study emphasizes the importance of adequate iron supplementation for brain health and prevention of neurological diseases.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies have demonstrated that iron chelators can reduce the MAO activity, suggesting that iron bioavailability can affect the MAO activity (Zheng et al, 2005; Gal et al, 2006). The underlying mechanism of induction of MAO-A activity in IR group is still unclear, but these results can help to explain the symptoms of depression reported in iron-deficient population (Corwin et al, 2003), since increased MAO-A activity has been linked to mood disorders (Meyer et al, 2009; Sacher et al, 2015; Kolla et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…1,9,40 The ability to image and quantify human brain MAO A with PET has enabled the investigation of relationships between MAO A levels and behavioral and disease phenotypes in healthy volunteers and in patients. [41][42][43] For example, PET studies have revealed elevations in brain MAO A activity in major depressive disorder (MDD) 44 and mood disorders, 43 whereas low MAO A activity has been related to maladaptive behavioral traits, such as aggression. 45 Interestingly, PET imaging has also demonstrated a modulating effect of the environment on brain enzyme levels by showing that current cigarette smokers have reduced brain MAO A.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments that use a model of a depression like state that is induced by immunization of rats against complexes of exogenous or endogenous MAO inhibi tors with a protein carrier have shown that these animals have increased MAO activity [26]. Patients with depres sion have enhanced receptor binding of MAO A [27] and increased 5 HT turnover in the brain regions [28].…”
Section: Discussionmentioning
confidence: 99%